y-11y=

Simple and best practice solution for y-11y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-11y= equation:


Simplifying
y + -11y = 0

Combine like terms: y + -11y = -10y
-10y = 0

Solving
-10y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-10'.
y = 0.0

Simplifying
y = 0.0

See similar equations:

| 7(-6)+3(-5)= | | (7c^2)(-6c^4)= | | x^4-30x^2-125=0 | | slopey=4x+5 | | 91/4+(-43/3)= | | x^4-30x^2+115= | | s(x+t)=tx-m | | (y^2+4y)-(y^2+10y)= | | (x^2-3xy)-(-2x^2+xy)= | | 2c-8= | | 1-3x=10x-20 | | 4(y+1)-3-5y=2(y-2) | | x+(12-x)=38 | | 4x^3=36 | | -19+8x=x-40 | | (2x^2-4y^2)+(6x^2-2xy+4y^2)= | | 4(y+1)-(3-5y)=2(y-2) | | t^31= | | (3x^2+9x)+(6x-24)= | | 24x^2-11x=0 | | 4(u+4)-7u=-1 | | 7x^2-3x-9=0 | | 32.12*p=3 | | 107+10x=97+15x | | 9x^2-38x+49=0 | | lne^7=y | | u^2-13u+42=0 | | 8-p=-12-13 | | -2x=-3x-2 | | e^7=x | | t^2-13t+2=0 | | M-11=27 |

Equations solver categories